Analisis Pola Agroforestri pada Kebun Petani - Fahruni Fahruni (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2015)
Peatland conditions fficted by fire eoch year in Central Kal,imantan, resulting in the disruption of the ecologicol balance. Agroforestry is an option on a solution to restore the function of peatlands. Through case study methodologt, the first phase includes the preparation of the necessary secondary data collection. The second stage is afield survey of data collection bioplrysical, socio-economic and agroforestry systems. The third stage is a data anolysis and presentation ofresearch results. Based on this research, there are three patterns of agroforestry conducted by people on peat, which is shaped agrisilvikultur, silvopasturo and agrosilvopsstura, where existing agroforestry pattern is the pattern of modern agroforestry. Financial analysis shows that the value of B/C ratio agrisilvikultur = 2.03, silvopastura B / C ratio = 2.68 and agrosilvopastura B/C ratio = 2.5. B /C ratio value is > l means agroforestry pattern is said to be finorrcially beneficial.